Methodology to Reduce Cooling Energy Consumption by Incorporating Pcm Envelopes: A Case Study of a Dwelling in Chile - Vasco-Calle, D; Tapia-Calderon, A (Elsevier Ltd, 2021)
The inadequate use of passive thermal conditioning alternatives, such as phase change materials (PCM), in Chile, despite the climatological advantages in various regions of the country and the need to improve thermal comfort indexes in many houses and buildings, is mainly due to cultural and economic reasons. Passive thermal conditioning measures entail economic benefits and an improvement in the quality of life. However, it is perceived as a luxury and not as an investment by many Chileans. We propose an optimized implementation methodology for PCM using a house belonging to the National Housing Monitoring Network (ReNaM) in Santiago, Chile. The strategic use of PCM is based on thermal comfort and occupancy. The proposed methodology improves the thermal comfort indexes and reduces the thermal loads of the building, resulting in lower energy consumption and CO2 emission. The proposed methodology also considers economic aspects to promote PCM as a passive alternative for thermal conditioning. © 2021 Elsevier Ltd